2017
DOI: 10.4018/jeco.2017010102
|View full text |Cite
|
Sign up to set email alerts
|

Comprehending Technology Attachment In The Case Of Smart Phone-Applications

Abstract: The purpose of this paper is to comprehend the causes and outcomes of smart phone application retention. To address this question, the authors propose a construct called app attachment and establish antecedents and consequences of the same. This study conceptualizes attachment with smart phone application as app attachment from a brand attachment perspective. Accordingly, app attachment is viewed as a two-dimensional construct composing of two measurement constructs namely app-self connection and app-prominenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…In addition, Peng et al (2014) validated the relationships between brand attachment and consumers' intention to use the branded app. Roy et al (2017) also established an association between brand attachment and two key variables (affective commitment and WOM) in India, along with the impact of the mobile app's presentation style, novelty and social connection to brand attachment. Hence, to the best of our knowledge, no study has as yet linked the concept of brand attachment to MSQ and WOM within the context of m-banking appsa literature gap that this study seeks to fill.…”
Section: Brand Attachmentmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, Peng et al (2014) validated the relationships between brand attachment and consumers' intention to use the branded app. Roy et al (2017) also established an association between brand attachment and two key variables (affective commitment and WOM) in India, along with the impact of the mobile app's presentation style, novelty and social connection to brand attachment. Hence, to the best of our knowledge, no study has as yet linked the concept of brand attachment to MSQ and WOM within the context of m-banking appsa literature gap that this study seeks to fill.…”
Section: Brand Attachmentmentioning
confidence: 89%
“…Despite its importance, the concept of brand attachment has been scarcely studied in a mobile context (Peng et al, 2014;Yang, 2016;Roy et al, 2017). Yang (2016) showed that consumer empathy is associated with brand attachment in the case of branded mobile apps.…”
Section: Brand Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, customers who are securely attached to the use of smartphone applications experience higher levels of trust, and dimensions related to technology attachment play a critical role in influencing perceptions of trust (Roy et al, 2017).…”
Section: Service Quality and Relationship Qualitymentioning
confidence: 99%
“…It is also known as post-acceptance of technology. There are only a few models available currently in IS literature that have investigated the subjects adjoining the actual use or continued use of technology (Roy et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%